International cooperation of Uzbekistan in the development of the Paralympic sports games - Normuminov, A. (Proximus Journal of Sports Science and Physical Education, 2024)
This article analyzes the international cooperation of the Republic of Uzbekistan in the development of the Paralympic movement. The article examines the work carried out within the framework of cooperation with international sports organizations of Uzbekistan, projects related to the training of athletes, training programs and infrastructure development. The article reveals Uzbekistan's efforts to develop Paralympic sports and its place in the international community.